Post-moderate-intensity exercise energy replacement does not reduce subsequent appetite and energy intake in adolescents with obesity. Issue 5 (29th November 2019) - Thivel, D.; Roche, J.; Miguet, M.; Fillon, A.; Khammassi, M.; Beaulieu, K.; Finlayson, G.; Pereira, B.; Miyashita, M.; Thackray, A. E.; Masurier, J.; Duclos, M.; et al.
Abstract: Exercise modifies energy intake (EI) in adolescents with obesity, but whether this is mediated by the exercise-induced energy deficit remains unknown. The present study examined the effect of exercise with and without dietary replacement of the exercise energy expenditure on appetite, EI and food reward in adolescents with obesity. Fourteen 12–15-year-old adolescents with obesity (eight girls; Tanner 3–4; BMI 34·8 (sd 5·7) kg/m 2 ; BMI z score 2·3 (sd 0·4)) randomly completed three experimental conditions: (i) rest control (CON); (ii) 30-min cycling (EX) and (iii) 30-min cycling with dietary energy replacement (EX + R). Ad libitum EI was assessed at lunch and dinner, and food reward (Leeds Food Preference Questionnaire) before and after lunch. Appetite was assessed at regular intervals. Lunch, evening and total EI (excluding the post-exercise snack in EX − R) were similar across conditions. Lunch and total EI including the post-exercise snack in EX + R were higher in EX − R than CON and EX; EX and CON were similar. Total relative EI was lower in EX (6284 (sd 2042) kJ) compared with CON (7167 (sd 2218) kJ; P < 0·05) and higher in EX + R (7736 (sd 2033) kJ) compared with CON ( P < 0·001). Appetite and satiety quotients did not differ across conditions ( P ≥ 0·10). Pre-meal explicit liking for fat was lower in EX compared with CON and EX + R ( P = 0·05). There was time by condition interaction between EX and CON for explicit wanting and liking for fat ( P = 0·01). Despite similar appetite and EI, adolescents with obesity do not adapt their post-exercise food intake to account for immediate dietary replacement of the exercise-induced energy deficit, favouring a short-term positive energy balance.